If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18=-3(-2-v)
We move all terms to the left:
18-(-3(-2-v))=0
We add all the numbers together, and all the variables
-(-3(-1v-2))+18=0
We calculate terms in parentheses: -(-3(-1v-2)), so:We get rid of parentheses
-3(-1v-2)
We multiply parentheses
3v+6
Back to the equation:
-(3v+6)
-3v-6+18=0
We add all the numbers together, and all the variables
-3v+12=0
We move all terms containing v to the left, all other terms to the right
-3v=-12
v=-12/-3
v=+4
| 11-2x=45 | | -1(-5+2t)=11 | | x+13.2=20.9 | | 486=((x^2)(1/4x))/3 | | 2b=20+0 | | 2(3-s)=14 | | 119-y=90 | | 2a+3-8a=5 | | 1458=(x^2(1/4x))/4x | | 6x+6x+21=18 | | -10=-2(5-3r) | | 16+x+52=90 | | 3(4+2q)=30 | | 57x=90 | | 12-x=x+4 | | 1458=x^2(1/4x)/4x | | 30.1/x=7 | | 8(8r+5)=7r-17 | | (3z+14)=35 | | 37=7x÷5 | | -8x-9=7x+6 | | x-7.8=11.3 | | 12x+-12=14 | | 22x+45=42x-15 | | 7-6n=17 | | 5^{x}=33 | | t+30+17t=642 | | 4m=5m−10 | | 17-7=6n | | 6m+10=48 | | (8x-7)+(2x+4)=180 | | 11x-8=16x-3 |